The linguistic-cultural image of parts of the human body (the head and its elements) perpetuated in German and Polish surnames - Lica, Zenon (Papers in Linguistics, 2021)
The article scrutinizes linguistic and cultural image of the human body, limited to the lexeme ‘head’ and shown in the light of Polish and German names extracted from existing anthroponymic lexicons. As the analysis showed, the method of describing petrified forms points to a model of human nomination based on characteristic features of human appearance, both in Polish and German. The expressive value of these types of surnames depends on the connotations that their appellative meanings trigger in the recipient’s mind. They will be associated with the description of the head and parts of it, which consists of information concerning its size, shape and colour. The face, which is at the front, is a representative part of the person and thus it is subject to the most comprehensive view, which is evident in the richness of the onymic material presented.